Chemical composition and antibacterial activity of the essential oil of Laurus nobilis leaves. Issue 4 (16th February 2022) - Nabila, Bekhti; Piras, Alessandra; Fouzia, Belabdelli; Falconieri, Danilo; Kheira, Guenaoui; Fedoul, Firdaous-Faiza; Majda, Sekkal-Rahal
Abstract: Chemical composition determination and in vitro antibacterial effect of Essential Oil (EO) of Laurus nobilis leaves grown North West Algerian conditions were investigated. Antibacterial activity was evaluated by the technique of the paper disc diffusion. Extractions were carried out with Clevenger apparatus and EO compositions were investigated by gas chromatography coupled to mass spectrometry (GC-MS) analysis. The oxygenated monoterpenes (MO) were the class with the highest contents, represent 59% of the EO. A total of twenty-seven of these compounds were identified, the major components were 1, 8-cineole (30.1%), α-terpynil acetate (21.6%), methyl eugenol (16.9%) of the total oil. The highest antibacterial power of the EO tested was recorded in Streptococcus faecalis and Staphylococcus aureus with the zone diameter of inhibition 13.6 and 11.2 mm respectively and a minimal inhibitory concentration (MIC) of 0.25 mg/mL for both these two strains. Graphical Abstract: